Navigating the shadow of fear: a qualitative study unveiling the lived experience of fear of cancer recurrence among Chinese gastric cancer survivors undergoing chemotherapy - Zhao, Haiyan; Zhou, Ye; Hou, Yuzhu; Liu, Yun (Frontiers in Medicine, 2025)
PurposeThis study aimed to gain an in-depth understanding of the psychological experience associated with the fear of cancer recurrence (FCR) among survivors of gastric cancer. Additionally, it sought to explore the triggering factors that trigger this fear and the coping strategies employed by individuals facing this challenge.MethodsThe Purposive sampling method was used to select study participants. A total of 20 survivors with gastric cancer who had undergone chemotherapy. Participants were recruited from a tertiary hospital in Jingjiang City, Jiangsu Province, and data collection took place from November 2023 to January 2025. Semi-structured, in-depth interviews were conducted during the chemotherapy sessions, with each interview lasting 30 to 45 min. The interview data were analyzed using the thematic analysis method.ResultsThe psychological experience of FCR among survivors of gastric cancer was categorized into three main themes: (a) Varied manifestations of the FCR: including self-perceptions, impact on family members, and the surrounding atmosphere; (b) Factors triggering the FCR: such as symptoms, treatment, environment, and future plans; (c) Coping strategies for the FCR: involving both positive and negative coping mechanisms.ConclusionRecognizing the pervasive nature of the FCR, it is essential to implement comprehensive interventions that encompass personal, family, and societal dimensions. Such interventions can help alleviate the sense of disease uncertainty experienced by survivors of gastric cancer. By adopting a holistic approach, a support model involving the hospital, family, and society can be developed to provide robust assistance for individuals navigating the challenges of cancer.